CONTRIBUIÇÃO DAS HISTÓRIAS EM QUADRINHOS COMO OBJETO DE APRENDIZAGEM PARA O ENSINO DE ECOFILOSOFIA NO ENSINO FUNDAMENTAL - Modesto, Sandro Luiz (2020)
The research carried out here is an experience of teaching Ecophilosophy in two classes of sixth year of elementary school at EMEF Professor Cerqueira Lima in the municipality of Cariacica - ES with a comic strip. The Ecophilosophy taught in this research